ความพร้อมและความต้องการของเกษตรกรผู้เลี้ยงโคนมในเขตพื้นที่องค์การส่งเสริมกิจการโคนมแห่งประเทศไทย (ภาคเหนือ) สำหรับการเข้าสู่มาตรฐานปศุสัตว์อินทรีย์ของประเทศไทย - สมภักดี ฌาน; ผลประไพ ชนัญ; สินเดชารักษ์ ธีระ (Thai Journal of Science and Technology, 2014)
บทคัดย่อ การศึกษาความพร้อมและความต้องการของเกษตรกรผู้เลี้ยงโคนมในเขตพื้นที่องค์การส่งเสริมกิจการโคนมแห่งประเทศไทย (ภาคเหนือ) สำหรับการเข้าสู่มาตรฐานปศุสัตว์อินทรีย์ของประเทศไทยโดยศึกษาความรู้ของเกษตรกรที่มีต่อระบบการผลิตปศุสัตว์อินทรีย์ รวมถึงความพร้อมและความต้องการของเกษตรกรผู้เลี้ยงโคนมในการเข้าสู่มาตรฐานปศุสัตว์อินทรีย์โดยใช้การวิจัยเชิงสำรวจในการเก็บรวบรวมข้อมูลจากเกษตรกรที่เป็นสมาชิกสหกรณ์โคนมและศูนย์รวบรวมน้ำนมดิบที่อยู่ภายใต้การส่งเสริมของ อ.ส.ค. ภาคเหนือในพื้นที่ 5 จังหวัด ได้แก่ เชียงใหม่ ลำพูน เชียงราย สุโขทัย และพิจิตร รวม 230 คนผลการศึกษาพบว่าเกษตรกรร้อยละ 53.04 มีความรู้เกี่ยวกับปศุสัตว์อินทรีย์ในระดับปานกลาง ส่วนใหญ่ขาดความรู้เกี่ยวกับการใช้พันธุ์สัตว์และขยายพันธุ์ในระบบปศุสัตว์อินทรีย์ การไม่ใช้ยาปฏิชีวนะหรือยาแผนปัจจุบันในการรักษาโรคสัตว์ และการไม่ใช้พันธุ์สัตว์ที่มาจากการดัดแปรพันธุกรรม (GMO) ส่วนการศึกษาความพร้อมในการเข้าสู่มาตรฐานปศุสัตว์อินทรีย์ พบว่าโดยภาพรวมเกษตรกรพร้อมดำเนินการตามข้อกำหนดวิธีการผลิตปศุสัตว์อินทรีย์ร้อยละ 65.80 และพบว่าโดยรวมเกษตรกรมีความต้องการได้รับการส่งเสริมการผลิตโคนมอินทรีย์อยู่ในระดับมาก ส่วนใหญ่ต้องการได้รับการส่งเสริมด้านการตลาดสูงสุด รองลงมาคือต้องการได้รับการฝึกอบรมการผลิตโคนมอินทรีย์ ต้องการได้รับการส่งเสริมสื่อบางประเภท และต้องการได้รับการส่งเสริมด้านบริการตามลำดับ คำสำคัญ : ปศุสัตว์อินทรีย์; เกษตรกรผู้เลี้ยงโคนม; อ.ส.ค.; ความพร้อม; ความต้องการ Abstract A study on readiness and requirements of dairy farmers in the operational area (northern region) of the dairy farming promotion organization of Thailand (D.P.O.) in Approaching Thai Agricultural Standard forOrganic Livestock. The main objectives of this research study have been focused on the general knowledge of dairy farmers on organic livestock farming systems, readiness and requirements for dairy farmer approaching Thailand Agricultural Standard for Organic Livestock.This research survey has been conducted by gathering data from those farmers who are members of dairy cooperatives and also from the raw milk collection center under the administration of DPO in the Northern covering 5 provinces which are Chiangmai, Lamphun, Chiangrai, Sukhothai, and Phichit totaling 230 respondents. The results revealed that the majority of the farmers possessed medium range of knowledge on organic livestock amounting to 53.04 %. The areas where the respondents lack knowledge were the points on non-adopted method of embryo transfers and hormones for livestock breeding, antibiotic medicine usage or modern medication for livestock remedy, and the points non-acceptance of genetically modified organism (GMO). This research study has shown significant findings from the readiness of the farmer respondents to pursue the guidelines to produce organic livestock as follows: 65.80 %. In this connection, dairy farmers are highly in need for organic livestock promotion. They mainly would like to be supported in the field of marketing promotion. Subsequently, they would like to get organic dairy farm production training: Regarding necessaryinformative media promotion. Lastly, the dairy farmers would like to get sufficient services. Keywords: organic livestock; dairy farmer; D.P.O.; readiness; requirement